The impact of price change on consumer choice of automobiles - Mohd Mustafa, Muszafarshah; Abdul Razak, Nor Azam (2007)
The objective of this paper is to examine whether a change in the price of a given model of national automobiles affects the choice of alternative car models by consumers. Four models of national automobiles - Saga 1.3cc, Saga 1.5cc, Wira 1.3cc, and Wira 1.5cc - are considered over the period 2000–2002. The results based on the conditional logit model indicate that all of the alternative models are substitutes to each other.